The Role of Financial Education, Additional Income and Consumption Patterns in Improving the Financial Resilience of Surabaya City Students - Feriona Ayurizta Iliyas; Amalia Tizka Zhahrina; Linda Afifah; Devi Nadia Agustina; Maria Yovita R. Pandin (Economy and Finance Enthusiastic, 2025)
Seeing the development of today's times, quite a lot can be a factor that affects the financial resilience of students. Looking at the facts, the majority of students still have difficulty in managing their consumption patterns and financial arrangements. Therefore, we compile this research to be able to provide understanding as well as useful insights for students in the process of financial management, managing additional income, consumption patterns to hopefully increase financial resilience for students. This research uses a quantitative approach through the Google form survey method that we have distributed to the scope of the city of students in the Surabaya City area. The place of our research and the preparation of this research is in Surabaya, East Java. The results of this study show that there is a relationship between the role of financial education, additional income and consumption patterns in increasing the financial resilience of students. Therefore, it is necessary to teach financial education as early as possible, so that it will increase understanding related to financial literacy for both children, students and adults.